Survey of symptomatic dermatologic disease in homeless patients at a shelter-based clinic - Caitlin Contag; Stefan E. Lowenstein; Sharad Jain; Erin H. Amerson (Our Dermatology Online, 2017)
This study aimed to survey the range of skin disorders diagnosed at a San Francisco clinic based in a temporary homeless shelter. We retrospectively reviewed 254 charts documenting encounters from 2011-2015 and collected demographic and historical data, along with skin disease morphology and location, clinical diagnosis, and recommended therapies. Of 254 charts reviewed, 136 (53.3%) recorded a dermatologic complaint. Diagnostic categories from most to least prevalent were inflammatory dermatoses, superficial fungal infections, wounds and trauma, infestations, bacterial infections, neoplasms, and viral infections. The most prevalent body location of the skin complaint was the lower extremity. The high prevalence of dermatologic disease underscores the importance of expanding dermatologic care for unhoused individuals. Many of the cutaneous diseases were preventable or treatable with low-cost interventions. The frequency of skin conditions affecting the lower extremity suggests that a foot and leg exam should be routine in clinical encounters with homeless patients.